Freshwater leech (Annelida: Hirudinida) distribution in the Canadian Province of Newfoundland and Labrador and adjacent regions: check-list, new records, new pigmentation forms, and Pleistocene refugia - Madill, Jacqueline; Hovingh, Peter (Zootaxa, 2007)
The freshwater leeches (Hirudinida) in the Province of Newfoundland and Labrador were investigated by examining theliterature, the Canadian Museum of Nature and the United States National Museum of Natural History records, and aleech survey. New pigmentation forms are described for Erpobdella punctata (Leidy) and Erpobdella obscura (Verrill).This is the first published record for Haemopis lateromaculata Mathers in Canada. Four species (Glossiphonia elegans(Verrill), Helobdella modesta (Verrill), Erpobdella punctata, and Erpobdella obscura) were found in both Labrador andNewfoundland with Erpobdella obscura common in Labrador and the other three species common in Newfoundland.Seven other species of leeches were less abundant in Newfoundland with 6 of these species very restricted in distribution.The abundance of leech species in Newfoundland and the paucity of leech species in Labrador suggested that theisland species were present in a Pleistocene refugium associated with Newfoundland or the Grand Banks. Post-Pleistocenebarriers to leech mobility are examined, and possible timing of colonization events is proposed in this model.